Improving the fatigue performance of porous metallic biomaterials produced by Selective Laser Melting. (1st January 2017) - Van Hooreweder, Brecht; Apers, Yanni; Lietaert, Karel; Kruth, Jean-Pierre
Graphical abstract: Abstract: This paper provides new insights into the fatigue properties of porous metallic biomaterials produced by additive manufacturing. Cylindrical porous samples with diamond unit cells were produced from Ti6Al4V powder using Selective Laser Melting (SLM). After measuring all morphological and quasi-static properties, compression-compression fatigue tests were performed to determine fatigue strength and to identify important fatigue influencing factors. In a next step, post-SLM treatments were used to improve the fatigue life of these biomaterials by changing the microstructure and by reducing stress concentrators and surface roughness. In particular, the influence of stress relieving, hot isostatic pressing and chemical etching was studied. Analytical and numerical techniques were developed to calculate the maximum local tensile stress in the struts as function of the strut diameter and load. With this method, the variability in the relative density between all samples was taken into account. The local stress in the struts was then used to quantify the exact influence of the applied post-SLM treatments on the fatigue life. A significant improvement of the fatigue life was achieved. Also, the post-SLM treatments, procedures and calculation methods can be applied to different types of porous metallic structures and hence this paper provides useful tools for improving fatigue performance of metallic biomaterials. Statement of Significance: Additive Manufacturing (AM) techniques such as Selective Laser Melting (SLM) are increasingly being used for producing customized porous metallic biomaterials. These biomaterials are regularly used for biomedical implants and hence a long lifetime is required. In this paper, a set of post-built surface and heat treatments is presented that can be used to significantly improve the fatigue life of porous SLM-Ti6Al4V samples. In addition, a novel and efficient analytical local stress method was developed to accurately quantify the influence of the post-built treatments on the fatigue life. Also numerical simulation techniques were used for validation. The developed methods and techniques can be applied to other types of porous biomaterials and hence provide new and useful tools for improving and predicting the fatigue life of porous biomaterials.